2010
DOI: 10.1016/j.neuron.2010.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Adolescence: What Do Transmission, Transition, and Translation Have to Do with It?

Abstract: Negotiating the transition from dependence on parents to relative independence is not a unique demand for today’s youth, but has a long evolutionary history (transmission) and is shared across mammalian species (translation). Yet, behavioral changes observed during this period are often described as delinquent. This review examines changes in explorative and emotive behaviors during the transition into and out of adolescence and the underlying neurobiological bases in the context of adaptive and maladaptive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
154
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(165 citation statements)
references
References 144 publications
(201 reference statements)
5
154
0
6
Order By: Relevance
“…Adolescence has been defined as the period from onset of puberty to independence from parents (68). The duration of adolescence, by this definition, is highly variable within and among human populations.…”
Section: Sexual Maturationmentioning
confidence: 99%
“…Adolescence has been defined as the period from onset of puberty to independence from parents (68). The duration of adolescence, by this definition, is highly variable within and among human populations.…”
Section: Sexual Maturationmentioning
confidence: 99%
“…For example, Merrill et al [4] explored 6-to 12-year-old boys' and girls' route learning performance and found moderate effect size. These age-related changes in cognitive performance have been associated with age-related changes in neural substrates [5][6][7]. Studies using structural and functional neuroimaging paradigms have identified a central role for frontal and parietal regions in cognitive development patterns [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the universal neurohormonal conditionings determining the process of development in adolescence, including sexual, emotional and social maturation, the onset of adolescence, its phases and termination vary among different communities and culturally different populations [1,2,3].…”
Section: Introductionmentioning
confidence: 99%